Facile Synthesis of Magnetic Copolymer Microspheres Based on Poly(glycidyl methacrylate-co-N-isopropylacrylamide)/Fe3O4 by Suspension Photopolymerization - Siti Zulaikha Mazlan; Faszly Rahim; Sharina Abu Hanifah (International Journal of Polymer Science)
Magnetic copolymer based on poly(glycidyl methacrylate-co-N-isopropylacrylamide) microspheres was prepared by 2,2-dimethoxy-2-phenylacetophenone- (DMPP-) photo initiated and poly(vinyl alcohol)- (PVA-) stabilized single step suspension photopolymerization. The effect of chemical interaction, morphology, and thermal properties by adding 0.1% w/v Fe3O4 in the copolymer was investigated. Infrared analysis (FTIR) showed that (C=C) band disappeared after copolymerization, indicating that the magnetic copolymer microspheres were successfully synthesized and two important bands at 908 cm−1 and 1550 cm−1 appear. These are associated with the epoxy group stretching of GMA and secondary amide (N–H/C–H) deformation vibration of NIPAAm in magnetic microspheres. The X-ray diffraction (XRD) result proved the incorporation of Fe3O4 nanoparticles with copolymer microspheres as peak of Fe3O4 was observed. Morphology study revealed that magnetic copolymer exhibited uniform spheres and smoother appearance when entrapped with Fe3O4 nanoparticles. The lowest percentage of Fe3O4 nanoparticles leached from the copolymer microspheres was obtained at pH 7. Finally, thermal property of the copolymer microspheres was improved by adding a small amount of Fe3O4 nanoparticles that has been shown from the thermogram.